Analisis Audit Tenure, Ukuran Perusahaan, dan Audit DeIay terhadap KuaIitas Audit pada Perusahaan Subsektor Pertambangan Batubara yang Terdaftar di BEI - Lubna Irhamna; M. Aryo Arifin; Nurmala, Nurmala (Penerbit Goodwood, 2024)
Purpose: This study tests the hypothesis of audit tenure analysis of the effect of firm size and audit delay on audit quality in coal subsector mining companies listed on the Indonesia Stock Exchange. Research methodology: This study used quantitative data from 18 companies listed on the Indonesian Stock Exchange. The sampling technique used a purposive sampling method, and the samples that met the criteria for research were 13 companies over five years, totaling 65 financial reports for the 2018-2022 period. methods of SPSS 27. Data were collected from the documentation. Results: The results of this research partially show that Audit Tenure has no significant effect on audit quality, with a significance value of 0.720 > 0.05. Firm size does not have a significant effect on audit quality (0.933 > 0.05). Audit Delay has a significant effect on audit quality with a significance value of 0.001 < 0.05. We simultaneously obtained a significant value of 0.002 < 0.05, so simultaneously audit tenure, firm size, and audit delay influence quality audits. Limitations: Audit researchers are involved in coal subsector mining companies listed on the Indonesia Stock Exchange. Contribution: The researcher’s contribution to Audit Tenure, Firm Size, and Audit Delay on Audit Quality